1999
DOI: 10.1002/(sici)1097-0185(19990601)255:2<212::aid-ar11>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Does the subepicardial mesenchyme contribute myocardioblasts to the myocardium of the chick embryo heart? A quail-chick chimera study tracing the fate of the epicardial primordium

Abstract: Morris (J. Anat., 1976;121:47-64) proposed that the subepicardial mesenchyme might represent a continuing source of myocardioblasts during embryonic and fetal development. Recent studies have shown that the epicardium and subepicardial mesenchyme, and the coronary vasculature are all derived from a region of the pericardial wall, called the proepicardial serosa. In avian embryos, the cells from the proepicardial serosa colonize the heart via a secondary tissue bridge formed by attachment of proepicardial villi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(74 citation statements)
references
References 52 publications
4
68
0
2
Order By: Relevance
“…[16,24,33-35]. However, whether epicardial cells contribute to formation of cardiac muscle has been controversial [25,36-40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,24,33-35]. However, whether epicardial cells contribute to formation of cardiac muscle has been controversial [25,36-40].…”
Section: Discussionmentioning
confidence: 99%
“…In chick, the PE forms asymmetrically on the right sinus horn and migrates to the dorsal surface of the ventricular myocardium via an extracellular matrix bridge, which connects the PE and myocardium [13-16]. Epicardial coverage proceeds over the myocardium in a sheet-like manner [17].…”
Section: Introductionmentioning
confidence: 99%
“…Cells from the pro-epicardium detach and attach on the beating ventricular surface to form the epicardium[14]. Subsequently epithelial cells of the epicardium undergo epithelial-mesenchymal-transition (EMT) to form mesenchymal cells that invade the developing myocardium[15]. A subset of these mesenchymal cells after EMT acquire migratory properties and invade the developing myo-fascial planes to occupy an interstitial position in between cardiac myocytes to become resident cardiac fibroblasts[16, 17].…”
Section: The Cardiac Fibroblast In Developmentmentioning
confidence: 99%
“…The AV-EPDCs derive from the AV-epicardium, which, just like the rest of the epicardium, with the exception of the epicardium found on the outflow tract [19,20], originates from the proepicardium [2123]. Until a few years ago, our knowledge of the importance of the epicardium in relation to the formation of the coronary vasculature, cardiac fibroblasts, and AV junction was largely based on experimental studies using avian model systems [2427]. More recently, however, our insight into the role of the epicardium in heart development has been significantly advanced by studies in the murine heart.…”
Section: The Role Of the Epicardium In Av Junction Developmentmentioning
confidence: 99%
“…The initial studies on the fate of EPDCs in the developing heart using avian models strongly suggested that EPDCs were able to migrate into the AV cushions [24,25]. These studies did, however, not provide much insight into the spatiotemporal contribution of the EPDCs to the respective leaflets.…”
Section: Contribution Of Epdcs To the Av Junctional Tissuesmentioning
confidence: 99%